Pengembangan Lembar Kerja Siswa (LKS) Berbasis Multiple Intellegence dengan Teknik Pembelajaran Circuit Learning Materi Sistem Pencernaan Pada Manusia di SMP - Najmi Lihayati; M Haviz; Rina Delfita; Najmiatul Fajar (Edusainstika: Jurnal Pembelajaran MIPA, 2021)
This research is motivated by the facts found in the field that the low optimization of the utilization of teaching materials used by students causes the low level of education in science learning materials at SMP NI Padang Panjang. Teaching materials are usually used in the form of worksheets that have not been able to increase the exploration and development of the potential of various kinds of intelligence possessed by students in the learning process. The purpose of this research is to produce valid and practical teaching materials in the form of worksheets based on multiple intelligences using circuit learning techniques on the human digestive system. The type of research applied through this activity is research and development using a 4-D model consisting of define, design, and disseminated stages. The LKS product was validated by 2 biology lecturers at IAIN Batusangkar and 1 science teacher and a practical trial by 20 students of SMP N 1 Padang Panjang using validation instruments and practicum instruments. The validity obtained by this worksheet is measured from the average validity with a result of 84.3% in the very valid category and the average practicality with a result of 90.9% in the very practical category, so that multiple intelligence-based worksheets with circuit learning techniques can be used.